Principles of patient and public involvement in primary care research, applied to mental health research. A keynote paper from the EGPRN Autumn Conference 2017 in Dublin. (1st January 2018) - Howe, Amanda
Abstract: Clinical research relies on patients being willing to participate in research projects, and making this possible for patients with mental health problems can be a particular challenge. In the modern era, many countries have seen a movement to give a stronger voice to patients both in choices around their care and in how research is conducted. How to achieve effective patient and public involvement (PPI) and to make the patients real partners in this effort is itself a subject of research evaluation. This opinion piece—based on a keynote lecture given at the European General Practice Research Network 2017 autumn meeting in Dublin—describes both the reasons for expanding PPI, how it can usefully be achieved, and how this may relate to the particular context of mental health. There can be moral, methodological or policy reasons for PPI. The three commonest models of good practice in PPI are the 'one off, ' the 'fully embedded' and the 'outreach' models. In research into common mental health problems in family practice, 'outreach' approaches that minimize commitment over time may work best. 'Expert patients' from mental health charities can sometimes play this role. PPI may be challenging and involve extra effort, but the gains for all may be considerable. Wonca Europe networks including EGPRN can extend this message and findings.